Diversidad de murciélagos (Orden Chiroptera-Blumenbach, 1779) en el área suburbana: ‘‘Ecoparque del Centenario’’ Zacatecas (Jóvenes en la Ciencia, 2024)
Bats are the second most diverse order of mammal species, however, due to their biology, it is difficult to establish sampling and population monitoring protocols, which causes the total species count to be underestimated. Our objective was to characterize the diversity of bat species present in the urban park ''Ecoparque Centenario" by monitoring with mist nets. During one year mist nets were placed and specimens were captured. According to the phenological concept of species, field keys were used for bat identification (Medellín et al., 2008), species accumulation curves were elaborated with non-parametric estimators to evaluate the sampling effort and the values of the Shannon, Margalef, Berger-Parker and Simpson inv. diversity indexes were obtained. Nine bat species were identified corresponding to 3 families: Vespertilionidae (7 spp.), Molossidae (1 sp.), and Phyllostomidae (1 sp.). The accumulation curves do not tend to asymptote and the values of ICE (n=12.99) and Chao 2 (n=14.9) suggest that there are approximately 5 more species to be recorded in the study area. The diversity indices presented the following values:  Margalef=2.401, Shannon=2.064, Berger-Parker=0.2857 and Gini-Simpson=0.8545, these values suggest that the diversity recorded is moderate.